PC1 and PC2 are proprotein convertases capable of cleaving proopiomelanocortin at distinct pairs of basic residues. - Benjannet, S (1991)
A recombinant vaccinia virus vector was used to coexpress the two candidate mouse prohormone convertases, PC1 and PC2, together with mouse proopiomelanocortin (POMC) in the constitutively secreting cell line BSC-40 and in the endocrine tissue-derived cell lines PC12 and AtT-20, which exhibit regulated secretion. Monitoring of POMC processing demonstrated the distinct cleavage specificities of PC1 and PC2, since in the cell lines analyzed (i) PC1 cleaves POMC into corticotropin and beta-lipotropin, (ii) PC2 cleaves POMC into beta-endorphin, an N-terminally extended corticotropin containing the joining peptide, and either alpha MSH or desacetyl-alpha MSH, and (iii) PC2 cleaves POMC at the five pairs of basic residues analyzed, whereas PC1 cleaves two of them preferentially, suggesting that PC2 has a broader spectrum of activity than PC1. These data are consistent with our hypothesis on the physiological role of PC1 and PC2 as distinct proprotein convertases acting alone or together to produce a set of tissue-specific maturation products in the brain and in peripheral tissues.